The optimal anticoagulant therapy for mechanical heart valves in a gallbladder cancer patient with hepatic metastases: A case report. Issue 37 (September 2018) - Yan, Yi-Dan; Su, Ying-Jie; Chen, Bo-Ya; Cui, Jiu-Jie; Zhang, Zai-Li; Xu, Qi; Gu, Zhi-Chun
Abstract: Rationale: Developing an optimal anticoagulant strategy poses a challenging task in patients with mechanical heart valves (MHVs) throughout their lifetime. We report an optimal anticoagulant therapy in a cancer patient with hepatic metastases after MHV replacement. Patient concerns: A 68-year-old female with MHVs suffered from gallbladder cancer with hepatic metastases. Her international normalized ratio (INR) fluctuated owing to the declined hepatic function. Diagnoses: Gallbladder cancer and hepatic metastases, with a history of mechanic aortic valve replacement and mitral valve replacement. Interventions: Warfarin was discontinued and Vitamin K1 was immediately administrated via intravenous infusion. low-molecular-weight heparin (LMWH) was regarded as a preferable option, and nadroparin at the dosage of 4100IU daily was administered. Outcomes: No adverse event occurred during the patient's hospitalization and two-week follow up after discharge. Lessons: LMWH may represent a reasonable alternative regarding the inhibition of thrombus and bleeding in MHVs carriers with cancer and hepatic metastases.